Pemberdayaan Umat Buddha di Jawa Tengah: Studi Kuantitatif tentang Budaya, Praktik Keagamaan, dan Pengembangan Komunitas - Yayuk Sri Rahayu (Jurnal Budi Pekerti Agama Buddha, 2025)
This study aims to identify and analyze the potential of Buddhist communities in Central Java Province in order to strengthen religious identity and enhance their social engagement as a minority group within a multicultural society. The study employs a quantitative approach, collecting data from 376 respondents through a structured questionnaire. The collected data were analyzed using descriptive statistical techniques and Pearson correlation analysis to examine the relationships among the studied variables. The findings indicate that six key factors significantly contribute to strengthening religious identity and the spiritual resilience of Buddhist communities, namely cultural preservation, arts and traditions, utilization of cultural heritage sites, community economic development, and the implementation of religious activities. Among these factors, regular religious activities and the use of temples as religious tourism destinations emerged as the most dominant factors in encouraging community participation, social solidarity, and the sustainability of Buddhist teachings. These findings underscore the importance of adopting a holistic and locally grounded approach in community development initiatives. This study offers important implications for the formulation of religious policies and the development of more inclusive, contextual, adaptive, and sustainable strategies for the empowerment of Buddhist communities at both regional and national levels.